An R2R3-MYB Transcription Factor RmMYB108 Responds to Chilling Stress of Rosa multiflora and Conferred Cold Tolerance of Arabidopsis - Dong, Jie; Cao, Lei; Zhang, Xiaoying; Zhang, Wuhua; Yang, Tao; Zhang, Jinzhu; Che, Daidi (Frontiers in Plant Science, 2021)
A sudden cooling in the early spring or late autumn negatively impacts the plant growth and development. Although a number of studies have characterized the role of the transcription factors (TFs) of plant R2R3-myeloblastosis (R2R3-MYB) in response to biotic and abiotic stress, plant growth, and primary and specific metabolisms, much less is known about their role in Rosa multiflora under chilling stress. In the present study, RmMYB108, which encodes a nuclear-localized R2R3-MYB TF with a self-activation activity, was identified based on the earlier published RNA-seq data of R. multiflora plants exposed to short-term low-temperature stress and also on the results of prediction of the gene function referring Arabidopsis. The RmMYB108 gene was induced by stress due to chilling, salt, and drought and was expressed in higher levels in the roots than in the leaves. The heterologous expression of RmMYB108 in Arabidopsis thaliana significantly enhanced the tolerance of transgenic plants to freezing, water deficit, and high salinity, enabling higher survival and growth rates, earlier flowering and silique formation, and better seed quantity and quality compared with the wild-type (WT) plants. When exposed to a continuous low-temperature stress at 4°C, transgenic Arabidopsis lines–overexpressing RmMYB108 showed higher activities of superoxide dismutase and peroxidase, lower relative conductivity, and lower malondialdehyde content than the WT. Moreover, the initial fluorescence (Fo) and maximum photosynthetic efficiency of photosystem II (Fv/Fm) changed more dramatically in the WT than in transgenic plants. Furthermore, the expression levels of cold-related genes involved in the ICE1 (Inducer of CBF expression 1)-CBFs (C-repeat binding factors)-CORs (Cold regulated genes) cascade were higher in the overexpression lines than in the WT. These results suggest that RmMYB108 was positively involved in the tolerance responses when R. multiflora was exposed to challenges against cold, freeze, salt, or drought and improved the cold tolerance of transgenic Arabidopsis by reducing plant damage and promoting plant growth.